Enhancing Primary Pupils’ Reading Interest through Illustrated Science Storybooks: A Sequential Explanatory Study - I Komang Wisnu Budi Wijaya; Made Hery Santosa; I Wayan Widiana (Jurnal Penelitian Pendidikan IPA, 2025)
This study examined the effectiveness of illustrated science storybooks in enhancing primary pupils’ reading interest within the Indonesian educational context. Responding to global concerns regarding declining reading motivation among young learners, the research explored how multimodal storybooks that integrate visual, narrative, and scientific elements may foster both cognitive engagement and emotional enjoyment. A Sequential Explanatory Mixed-Methods approach was applied with 17 third-grade pupils in Bali. The quantitative results demonstrated a substantial and statistically significant improvement in reading interest, with the mean score increasing from 51.10 to 78.40 (p < .001), indicating consistent gains across all motivational dimensions. Qualitative findings supported these results, revealing heightened curiosity, sustained emotional and cognitive engagement, and increased persistence in independent reading. Collectively, the findings suggest that illustrated science storybooks not only enhance motivation but also stimulate deeper engagement with science-related texts. The study contributes to theoretical understandings of Multimodal Learning and Self-Determination Theory and offers practical guidance for integrating illustrated storybooks into literacy and science instruction to promote scientific curiosity and sustained reading habits among primary pupils.